Pengaruh isolat protein kedelai (IPK) dalam pembuatan kerupuk dari bahan dasar nasi dan tepung tapioka terhadap sifat fisik dan sensoris - Sukamto Sukamto (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2024)
Crackers are a popular food consumed by Indonesian people as a side dish or as a snack. The quality of crackers is determined by their swelling power, crunchiness, taste and nutritional value. Crackers are generally made from tapioca flour, so the protein component is low. Therefore, this research utilized soy protein isolate which was added to tapioca and rice dough ingredients to increase the protein content of crackers. The aim of the research is to find the best formula for adding soy protein isolate and thick slices to produce crackers that contain high protein. The research method was experimental, the first treatment factor was the addition of soy protein isolate to the tapioca flour and rice mixture. The second factor is the thickness of the cracker slices. The treatment design was a Completely Randomized Design (CRD) with a 4 X 4 factorial pattern which was repeated 3 times. The research results showed that the interaction effect between the use of soy protein isolate in dough with various slice thicknesses resulted in significant differences in the swellability of crackers, frying time and oil absorption capacity. The average sensory properties of crackers added with soy protein isolate were favorable at a slice thickness of 1mm-1.5mm. The conclusion is that the best formula for making crackers made from tapioca flour and rice is to use 5% to 7.5% soy protein isolate, and the thickness of the cracker slices is 1mm – 1.5mm.